Evaluation of disease distribution and drug utilization for management of psoriasis patients in dermatology OPD of a tertiary care centre: a retrospective observational study - Badar, Vandana; Chavan, Rachana R.; Chokhandre, Mrunalini; Pradhan, Kalyani (International Journal of Research in Medical Sciences, 2023)
Background: Psoriasis is a chronic skin disorder that can have different clinical presentations. Topical corticosteroids are the primary therapy for psoriasis, but there are many new drug options approved for its treatment. The aim of this study was to assess the prescription patterns and disease distribution of psoriasis patients in a tertiary care center in central India. Methods: We conducted a retrospective observational study of 195 psoriasis patients treated in the Dermatology OPD of a teaching hospital from September 2020 to June 2021. We analyzed patient data for demographics, disease characteristics, and medications prescribed using frequency distributions in Microsoft Excel. Results: Plaque psoriasis was the most common clinical variant among the patients, and the male to female ratio was 1.5:1. February had the highest number of patients treated, indicating an aggravation of symptoms during cold weather. Most patients (93.33%) were prescribed topical corticosteroids, with clobetasol being the most commonly used medication (78%). The average number of drugs per prescription was 5, with other drugs prescribed including emollients (53.33%), vitamin D (31.7%), anti-histamines (21.02%), and methotrexate (5.1%). Conclusions: Topical corticosteroids, particularly clobetasol, were the most commonly prescribed medication for psoriasis patients in this study. Multiple drugs were needed for the management of most patients. The study provides insights into the prescription patterns of psoriasis medications, which may improve patient care and outcomes.